2012
DOI: 10.2514/1.c031227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Concepts for Operations in Metroplex Terminal Area Airspace

Abstract: Metropolitan areas with high traffic demand are often served by a system of two or more airports whose arrival and departure operations are highly interdependent. Such an airport system is referred to as a metroplex. A temporal-spatial framework for evaluating concepts for improving metroplex operations was developed. In this framework, concepts for metroplex operations were defined by their spatial and temporal impacts on operations. These impacts were evaluated parametrically with a generic metroplex model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In turn, the generic model was extended to the North California Metroplex to quantify the benefits of NextGen PBN. Ren et al [4] also developed a generic metroplex model based on a linked nodes queueing process to evaluate the spatial and temporal impacts from a metroplex and found that temporal scheduling and route segregation can reduce delays in terminal area airspace.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, the generic model was extended to the North California Metroplex to quantify the benefits of NextGen PBN. Ren et al [4] also developed a generic metroplex model based on a linked nodes queueing process to evaluate the spatial and temporal impacts from a metroplex and found that temporal scheduling and route segregation can reduce delays in terminal area airspace.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Metroplex Simulation Environment (MSE) is another platform that can be used to rapidly-assemble a purposebuilt simulation [10]. Clark conducted the simulation in the New York terminal area space using SIMMOD to assess the metroplex model [4]. Although there are a number of simulation and modeling tools that can satisfy air traffic simulation needs, they tend to be expensive and difficult to use, and extensive training is needed for configuring and running them.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, while such measures may result in locally improved solutions for an individual airport, they are often sub-optimal for the system of airports, and pose numerous difficulties in their widespread deployment due to a lack of transferability. In view of this, a number of generic attempts have been made to improve Metroplex operations, including: improved aircraft scheduling, optimized capacity trade-offs and optimized infrastructure planning (McClain, 2013;Clarke et al, 2012;Atkins et al, 2011;Donaldson and Hansman, 2011;Ramanujam and Balakrishnan, 2009;de Neufville, 1995;Hansen, 1995;Hansen and Weidner, 1995;Hansen and Du, 1993). However, all these approaches are limited by the current terminal airspace structure, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies regarding the reduction in fuel consumption and emissions with CDAs have been evaluated by Wubben and Busink, 11 Clarke et al, 12,13 van Boven, 14 Hartes et al, 15 and Itoh and Uejima. 16 Fuel savings of more than 40 kg and 2 min less flight time per flight were obtained by Turgut et al 17 at only one airport in Istanbul Airport TMA.…”
Section: Introductionmentioning
confidence: 99%